Morphology controlled Co-precipitation method for nano structured transparent MgAl2O4. Issue 17 (1st December 2017) - Nam, Sangwoo; Lee, Munkeun; Kim, Byung-Nam; Lee, Younghwan; Kang, Shinhoo
Abstract: MgAl2 O4 spinel nano powders with various morphologies were synthesized with ammonium aluminum carbonate hydroxide by carbonate precipitation. The powders with rod, corn, and spherical morphologies were synthesized, varying the concentration of ammonium ions, by growth and aggregation of nano precipitates. The powders with spherical morphology formed spinel phase at a lower calcination temperature than those with other shapes. The morphology provided a superb sinterability due to improved particle packing. Although the synthetic conditions resulted in a composition slightly off the stoichiometric composition with Mg loss, this provided a proper condition for inhibiting grain growth. Finally, Mg-spinel which was obtained from spherical particles and fabricated by spark plasma sintering (SPS) showed much improved transparency with an average grain size of 200 nm (RIT and TFT are 55.92% and 63.75% at 550 nm 75.35% and 78.91% at 1500 nm, respectively) than those from other shaped particles.